MYKOLA LEONTOVYCH’S PEDAGOGICAL LEGACY IN PODILLIA (LATE 19TH AND EARLY 20TH CENT.) - Zuziak, Tetiana; Lavrinenko, Oleksandr; Rohotchenko, Oleksii; Marushchak, Oksana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the article is to reveal the essence of pedagogical ideas of Mykola Leontovych, a composer and an educator, who defended the need for a closer connection of pedagogy and art, particularly in the field of professional training of future teachers in Podillia region of Ukraine during the late 19th into the early 20th centuries. The methodology of the study is based on the application of historical, chronological, cultural, and axiological approaches, which place the evolution of M.Leontovych’s views in a broad socio-cultural context. The creative scientific approaches of M.Leontovych regarding the necessity of mastering art in the system of vocational training of future teachers were emphasized; the basic principles of the interrelation of art and pedagogy in forming the personality of future teachers were substantiated.